Life Cycle Assessment for Hydrothermal Carbonization of Urban Organic Solid Waste in Comparison with Gasification Process: A Case Study of Southern Chile - Cubillos-Montecino, F; Diaz-Robles, L; Espinoza-Perez, A; Vallejo-Gallardo, F (John Wiley and Sons Inc, 2021)
Most developing countries lack sufficient legal and management infrastructure to dispose of urban solid waste (USW). The continuous increase of USW generation requires evaluating different treatments for developing countries based on the life cycle assessment methodology to compare the environmental impact by reducing greenhouse gases and leachate. Hydrothermal carbonization (HTC) and gasification processes are presented as potential solutions for USW treatment due to their efficiency in producing energy for local requirements. This study aimed to compare both technologies for Temuco and Padre Las Casas cities in Southern Chile that show severe air pollution and USW management problems. The results indicated that gasification had a better environmental performance than HTC when the conversion of 1 ton of organic fraction USW was analyzed. However, since HTC achieved higher energy efficiency, it had a lower environmental impact than gasification, considering the production of 1 MWh. For a definitive choice of the technology to be used, it is necessary to compare other variables, including economic and social aspects, to provide a holistic perspective. © 2021 American Institute of Chemical Engineers.